Artificial intelligence integration in a web-based e-storyboard system: A 4D framework for advancing interactive multimedia design - Budiarti, Marlinda Indah Eka; Arsyad, Rahmatullah bin; Fathurahman, Muhammad; Kahar, Muhammad Syahrul; Payapo, Fatmawati (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to develop an AI-assisted e-storyboard that is accessible through a web-based platform and to examine its validity and practicality for supporting students in designing interactive multimedia learning materials. Method: The study employed a research and development approach using the Four-D (Define, Design, Develop, and Disseminate) framework. Data were collected from mathematics education students and expert validators at Muhammadiyah University Sorong through needs-analysis questionnaires, expert validation instruments, and student response questionnaires. The collected data were analyzed descriptively using percentage-based criteria to determine the validity and practicality of the developed system. Findings: The developed e-storyboard integrates artificial intelligence features that provide recommendations for visual, audio, textual, and animation elements based on user input. Expert validation results indicated that the product achieved a high level of feasibility across language, content, and media aspects, with an overall validity score of 91.25 percent. Student responses also demonstrated strong acceptance of the system, with a practicality score of 87 percent. Although minor technical challenges were reported in relation to certain interactive components, the majority of users found the platform easy to use, engaging, and helpful in structuring multimedia design tasks. Significance: The findings indicate that the AI-assisted web-based e-storyboard is both valid and practical as a tool for interactive multimedia planning. By offering real-time recommendations and collaborative features, the system reduces common difficulties associated with manual storyboard development and supports a more efficient and structured multimedia design process. This study contributes to the advancement of educational technology by demonstrating how artificial intelligence can be meaningfully integrated into instructional design frameworks to support student creativity and learning.